1979
DOI: 10.1071/pp9790379
|View full text |Cite
|
Sign up to set email alerts
|

Solute Accumulation in the Apex and Leaves of Wheat During Water Stress

Abstract: Accumulation of several low-molecular-weight solutes was measured in the developing floral apex, in an enclosed, elongating leaf, and in an expanded leaf of wheat plants during a 13-day period of water stress. In the apices and enclosed leaves, osmotic potential fell from - 1.2 to -4.0 MPa. The main contribution to the decline in osmotic potential during the first 3 days of stress was from an increase in the content of ethanol-soluble carbohydrate. Later, increases in the concentrations of both carbohydrates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
1
9

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(87 citation statements)
references
References 0 publications
10
67
1
9
Order By: Relevance
“…potential could be explained by contribution of minerals, of which potassium was dominant. The major role of potassium and free amino acids was also shown in leaf bases of cereals subjected to rapid (3 d) desiccation (Munns et al, 1979 ;Barlow et al, 1980). However, in our study, amino acids and proline contributed by less than 2-3 % to bulk osmotic potential, which was about twice as great in ryegrass as in cocksfoot.…”
Section: Contribution Of Solutes To Osmotic Potentialmentioning
confidence: 99%
“…potential could be explained by contribution of minerals, of which potassium was dominant. The major role of potassium and free amino acids was also shown in leaf bases of cereals subjected to rapid (3 d) desiccation (Munns et al, 1979 ;Barlow et al, 1980). However, in our study, amino acids and proline contributed by less than 2-3 % to bulk osmotic potential, which was about twice as great in ryegrass as in cocksfoot.…”
Section: Contribution Of Solutes To Osmotic Potentialmentioning
confidence: 99%
“…Among the major effects are those involving carbohydrate metabolism, with the accumulation of sugars and a number of other organic solutes [75]. Munns et al, (1979) [76] and Quick et al, (1992) [60] showed that sugars are major contributors to osmotic adjustment in expanding wheat leaves. Moreover, short-term water stress inhibited starch synthesis more strongly than sucrose synthesis, in both ambient CO 2 and in saturating CO 2 .…”
Section: Carbohydrates Changes Under Water Stressmentioning
confidence: 99%
“…In general, one of the important pathways to enhance water stress and salt tolerance is through osmotic adjustment (OA), in which leaf turgor remains necessary for stomatal opening and, thus, sustains photosynthesis and growth (Huang et al, 2010;Nio et al, 2011). Besides, various types of compatible solutes accumulate, such as sugars, proline, gycinebetaine or potassium, among others (Munns et al, 1979;Morgan, 1992;Nio et al, 2011), and can increase. These compounds can be added to the list of the non-enzymatic antioxidants that plants need to counteract the inhibitory metabolic effects of reactive oxygen species (ROS) provoked by stress (Gill & Tuteja, 2010;Penella et al, 2014aPenella et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%